MENERAPKAN MODEL ACCELERATED LEARNING DALAM PEMBELAJARAN AKUNTANSI: SEBUAH PEDOMAN UNTUK DOSEN-DOSEN AKUNTANSI - SETIN SETIN (Jurnal Bisnis dan Akuntansi, 2007)
This article aims to give an understanding that learning with accelerated learning approach is very important and explain how to design Accountancy with accelerated learning approach. The outline emphasizes on three things. First, the concept of accelerated learning. Second, model of accellerated learning. Third, the usage of accelerated learning in designing Accountancy. Accelerated learning model in this article emphasizes on the emotional side of students. There are four keywords of accelerated learning model (grow, doing, named, demonstrate, repeat and celebrate). This model is a result of collaboration between quantum teaching model (1999) and genius learning strategy model (2003).